P004: Effect of telephone triage (811) calls on a regional poison centre. (May 2019) - Alrobaian, S.; Hurley, K.; Fitzpatrick, E.; Mosher, L.; Young, M.; Murphy, N.; Matheson, K.
Abstract : Introduction : Telephone Triage Services (TTS) manage phone calls from the public regarding general medical problems and provide telephone advice. This telephone based care can overlap with care provided by Poison Centres. Our objective was to examine the impact of a provincial 811 TTS on the IWK Regional Poison Centre (RPC).Methods : This is a retrospective descriptive study using interrupted time series methodology. We compared monthly IWK RPC call volume in the pre-811 era (January 2007-July 2009) and the post-811 era (September 2009-December 2017). We summarized the characteristics of callers who accessed the IWK RPC in terms of client age, sex, intentionality, time of day, call disposition and outcome. Caller characteristics were compared between the pre- and post-811 eras using chi-square test for categorical variables. We used segmented regression analysis to evaluate changes in slope of call volume in the pre- and post 811 eras. The Durbin-Watson statistic was performed to test for serial correlation and the Dickey-Fuller test to investigate seasonality.Results : The dataset included 82683 calls to the IWK RPC – 27028 pre-811 and 55655 post-811. Overall, 55% of calls were for female clients and the largest age group was children aged 0-5 years (37%). Most calls originated from home (47%), followed by a health care facility (23%). Most calls were managed at home (65%). Less than 3% of calls resulted in major effect or death. The Durbin Watson statistic was not statistically significant (p = 0.94). The Dickey-Fuller test indicated series stationarity (p = 0.001). There was no statistically significant change in call volume to the IWK RPC due to the introduction of 811 (p = 0.39). There was no significant variation by time of day, day of week or month, with most calls occurring in the evening. There were significantly more calls regarding intentional ingestions in the post-811 era (23% vs. 19% pre-811, p < .001). Outcomes in the pre and post 811 eras were as follows: minor/no effect/non-toxic/minimal 80% vs. 78%; moderate 7% vs. 10%; and, major/death 1.7% vs. 2.0%.Conclusion : The introduction of a TTS did not change call volumes at our RPC. The increase in the percentage of calls about intentional ingestions may reflect an increase in call acuity as the 811-TTS likely manages calls about minor/non-toxic ingestions without consulting with the RPC. Our future research will examine the nature of poison related calls to the 811-TTS.